2010
DOI: 10.1016/j.mvr.2010.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell activation in a VEGF-A gradient: Relevance to cell fate decisions

Abstract: Distribution of vascular endothelial cell growth factor A (VEGF-A) as a gradient determines microvascular endothelial cell (EC) fate during organogenesis. While much is understood about mechanisms of differential distribution, less is known about how EC perceive and interpret a graded VEGF-A signal to generate positional target gene activation. Using microvascular EC, we analyzed the effect of time and graded VEGF-A input on VEGFR2 autophosphorylation, signal kinase activation and induction of immediate-early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
41
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 40 publications
4
41
0
Order By: Relevance
“…25,[52][53][54][55][56][57] The central role of VEGF-A among these signals has been demonstrated in numerous experimental contexts. 21,23,33,34,[58][59][60] In line with findings from embryological studies, endothelial network morphogenesis in our in vitro constructs is critically dependent on VEGF-A, as evidenced by near-complete ablation of network formation with 2 mg/mL of sVEGFR1-Fc (Fig. 2D).…”
Section: Discussionsupporting
confidence: 89%
“…25,[52][53][54][55][56][57] The central role of VEGF-A among these signals has been demonstrated in numerous experimental contexts. 21,23,33,34,[58][59][60] In line with findings from embryological studies, endothelial network morphogenesis in our in vitro constructs is critically dependent on VEGF-A, as evidenced by near-complete ablation of network formation with 2 mg/mL of sVEGFR1-Fc (Fig. 2D).…”
Section: Discussionsupporting
confidence: 89%
“…[25,26], these findings indicate that InsP 3 -dependent Ca 2þ release occurs less frequently at high [VEGF] in ECFCs, likely due to a decrease in InsP 3 production during the Ca 2þ burst. This feature is supported by a recent study of PLC-c phosphorylation by VEGFR-2, according to which signal duration is longer in HMVECs exposed to lower ligand concentrations [51].…”
Section: Discussionsupporting
confidence: 61%
“…Such variability in the Ca 2þ response to extracellular hormones or growth factors has already been reported in a number of ECs both in vitro [29,38,49] and in situ [50]. Moreover, the differential activation of jagged1 and DII4 in the Notch signaling pathway and of mitogen activated protein kinases has already been described in ECs exposed to the same VEGF concentration [51,52]. The dissimilar response of ECs from the same coverslip to VEGF might be due to the wide variation in VEGFR-2 levels, as only approximately 60% of ECFCs express it [20].…”
Section: Discussionmentioning
confidence: 58%
“…For instance, the differential activation of jagged1 and DII4 in the Notch signaling pathway determines the distinct fate (tip vs. stalk) of two adjacent endothelial cells exposed to a VEGF gradient during the angiogenic process [85]. A recent study has further demonstrated that the mitogen-activated protein kinase pathway is triggered by VEGF in individual microvascular endothelial cells, whereas their adjoining cells are silent [86]. The dissimilar response of neighboring cells to VEGF might be linked to the wide variation in VEGFR-2 levels, as only about 60% of UCB-ECFCs express it (unpublished data from our group).…”
mentioning
confidence: 99%